Repair of avulsion flap injury of heel by multiple point anchorage using Kirschner wires-a case series - Jain, Prateek; Tathe, Pankaj; Arora, Chandan; Sakharkar, Nilesh; Adewar, Aniket; Sarode, Rohan (International Journal of Research in Orthopaedics, 2022)
The heel pad is a dense band of fibrous tissue with complex anatomy. Injuries to heel pad are uncommon but very challenging due to its precarious blood supply. In this study we tried fixing acute heel pad avulsion injuries using multiple Kirschner wires and results were evaluated according to the American orthopedic foot and ankle society hind foot score. Results were excellent for 3 -out of 9 patients and good for 6 patients according to the AOFAHS scoring system. Anchorage of acute heel pad avulsion injuries using multiple Kirschner wires is an effective and reliable treatment modality.